Desenvolvimento e avaliação de lipossomas contendo a naftoquinona sintética ENSJ39: estudos in vitro e in vivo - Rebouças, Luciana de Vasconcelos (2020)
Cancer is a public health problem in world, characterized by uncontrolled cell proliferation. Nanotechnology is gaining prominence for mitigating the side effects of conventional chemotherapy treatments and for developing nanoparticulate systems that allow greater biodistribution, bioavailability, site-specificity, less toxicity, reduces resistance, and improves therapeutic efficacy. This study aimed to encapsulate the synthetic naphthoquinone ENSJ39 (a compound with high cytotoxic activity in vitro, but with hydrophobic characteristic) in liposomes, characterize them and evaluate their biological activity in vitro and in vivo. Liposomes were obtained by hydration method of the lipid film and subjected to physico-chemical characterizations (thermogravimetric analysis, differential exploratory calorimetry, dynamic light scattering technique and atomic force microscopy), evaluation of the encapsulation efficiency and studies of stability that included simulation transport and storage conditions. In vitro cytotoxicity test by MTT, Trypan blue exclusion assay and evaluation of morphological changes in tumor lineage were also analised. Subsequently, the liposomes were evaluated in vivo for acute toxicity and the LD50 of ENSJ39 was verified by the Up and Down method. Liposomes containing ENSJ39 showed a high encapsulation rate (82.3% ± 0.04), average size of 31 (± 5.81) nm, a zeta potential of +53.5 mV and a polydispersity index of 0.24. Up to 250° C, the liposomes were thermally stable, able to preserve the loss of mass of the free drug, and after 4 months of storage they maintained good physical-chemical characteristics. The IC50 values of the encapsulated drug showed no statistically significant difference when compared to free drug and the morphological evaluation in HCT-116 (colorectal), after 72 hours of treatment, showed the LE39 caused swelling and intense cytoplasmic vacuolization, in addition to promoting an increase in number of non-viable cells, similar to ENSJ39, when compared to negative and positive controls (doxorubicin). LD50 of the free compound was not defined due to the poor solubility, however, the highest dose tested (175 mg/kg) did not cause death of the animals. Both doses evaluated (55 and 175 mg/kg) of ENSJ39 and its encapsulated form, in acute toxicity test, did not cause changes in weight, behavior, renal biochemical, hepatic and hematological parameters. However, renal histopathological study showed changes in the animals that received the free drug via oral (55 mg/kg) and intraperitoneal (55 and 175 mg/kg). In conclusion, ENSJ39 encapsulation method was effective in obtaining stable liposomes, was able to improve the dispersion of this compound in an aqueous vehicle and was able to prevent damage to the renal tissue of mice compared to the free drug.